Discriminatory performance of adiponectin and leptin in the identification of impaired glucose tolerance: the Guangzhou Biobank Cohort Study - Cardiovascular Disease Subcohort - Toulis, Konstantinos A.; Thomas, G. Neil (PLOS ONE, 2018)
Background To evaluate the additional discriminatory performance of adiponectin, leptin, and their ratio in the identification of impaired glucose tolerance (IGT) in men and women without diabetes on top of conventional risk factors. Methods & results A total of 698 subjects underwent an oral glucose tolerance test (oGTT) and adipocytokine measurements. A comprehensive stepwise selection procedure was performed, followed by c-statistics and integrated discrimination improvement (IDI) analysis. In males, adiponectin levels were significantly lower in the IGT group compared to the non-IGT group (Whitney U test, p < 10-4), whereas leptin levels were significantly higher (p = 0.009) in IGT group. In females, adiponectin and leptin levels were not significantly different between groups (Mann-Whitney U test, p = 0.073 and p = 0.08, respectively). Adjusting for the most informative, sex-specific, clinical and biochemical factors, adiponectin, leptin and their ratio were not found to be significant predictors of the response to the glucose load, when modelled as continuous terms or tertiles. In males, the area-under-the-curve (AUC) for adiponectin was estimated at 0.620 (95% CI: 0.558-0.682) and the addition of adiponectin into the basic model provided a ΔAUC benefit of 0.004, showing no additional discriminatory benefit on top of conventional risk factors (IDI p-value: 0.27), nor did the addition of leptin or their ratio. The results were similar in females. Conclusions In Chinese individuals without diabetes, no significant evidence for the potential discriminatory value of adiponectin, leptin or their ratio in the identification of IGT on top of conventional risk factors was observed.
Gesehen am 30.04.2019